Effect of Au Grown on GaAs Substrate for Applying as Counter Electrode on Conversion Efficiency of Dye-Sensitized Solar Cells - Gurbuz, O.; Kirsoy, A.; Kilicarslan, F. A.; Erden, I.; Bozdogan, A. Celik; Firat, Y. (AMER SCIENTIFIC PUBLISHERS, 2016)
The symmetric Bis(4-fluorophenyl)-methoxy phthalocyanine (H2Pc) and its complexes (ZnPc and CoPc) were synthesized and studied photovoltaic properties of these compounds with the applicability of these synthesized compounds in dye-sensitized solar cells (DSSCs) as photosensitizers. Au thin film was grown on (100) oriented GaAs substrates by thermal evaporation technique for applying as counter electrode (CE) in DSSCs. The as-prepared Au/GaAs electrodes, assembled with this material as CE, were confirmed as substitution for platinum (Pt) counter electrode in DSSCs. The DSSC based on Au/GaAs thin films CE achieves power conversion efficiency (PCE) of 1.72%. The DSSC based on ZnPc exhibited significantly photovoltaic activities than metal free (H2Pc) and metal complexes (CoPc). Electrochemical impedance spectroscopy (EIS) demonstrated that the Au/GaAs as CE is effective for tri-iodide reduction. We presume that this study will open a way to fabricate DSSC devices with a CE based on Au/GaAs electrodes.
Keywords: Counter Electrode; Photovoltaic Cell Efficiency; GaAs; DSSC; OPTICAL-PROPERTIES; ORGANIC-DYES; METAL-FREE; LOW-COST; PERFORMANCE; PHOTOANODE; Energy & Fuels